Granulometric and Mineralogical Characterization of Sands from the Middle Course of the Kasai River (Ilebo Territory, Kasai Province, DRC) - Kitshabi, Lowny Trésor Madienga; Tshiwisa, Ivon Ndala Tshiwisa; Muke, Modeste Kisangala; Thomas Kanika Mayena, Thomas Kanika; Osomba, Dominique Wetshondo Osomba; Nkula, Valentin Kanda; Asidi, Djonive Munene; Makutu, Adalbert-Jules (Indonesian Journal of Earth Sciences, 2024)
This study addresses sediment dynamics within the fluvial system of the middle Kasai Basin, specifically between Ilebo town (pk605) and the confluence with the Loange River (pk525). The primary aim is to characterize the granulometric and mineralogical evolution of sand bars in the Kasai River, which pose navigational challenges in this section of the basin. The study seeks to answer the following question: How do the granulometric and mineralogical characteristics of sands transported by the middle course of the Kasai River evolve? The research employs laboratory granulometric techniques. Twenty sand samples were collected from sand bars along the middle and navigable course of the Kasai River during the flood recession period, ranging from upstream to downstream. Sieving was conducted using an AFNOR-type sieve column, followed by sedimentometric analyses and the calculation of various Folk & Ward textural parameters using the Excel program Gradistat. Additionally, six samples underwent automated mineralogical analysis using a QEMSCAN FEG Quanta 650. Granulometric analysis revealed that the sands from the middle course of the Kasai River are unimodal, with fine to medium grains in the granulometric fraction ranging from 186.2 µm to 426.8 µm. Most of these sands are moderately to well graded, with grains showing granulometric symmetry and, less commonly, fine asymmetry. Their kurtosis is largely mesokurtic, with occasional leptokurtic and platykurtic characteristics, indicating multiple depositional environments. The study demonstrates that the evolution of these granulometric parameters is uneven along the middle course of the Kasai River, though overall, the parameters exhibit limited variation. This suggests minimal and regular sediment inputs, consistent with the relative regularity of granulometric variations in environments characterized by free sedimentation. Automated mineralogical analysis identified a diverse mineralogical assemblage, dominated by quartz, followed by calcite, iron oxides, orthoclase, plagioclase, and kaolinite. Additionally, a group of minerals that do not exceed the 0.55% threshold—such as illite, apatite, ilmenite, muscovite, chlorite, biotite, montmorillonite, rutile, pyrophyllite, siderite, zircon, and dolomite—was identified. Consequently, the mineralogical evolution is not uniform throughout the middle course of the Kasai River, showing a sawtooth variation. This study clarifies the evolution of the granulometric parameters of Kasai River sands, which are influenced by the river's hydrodynamic regime. It also elucidates the mineralogical evolution, linked to the petrographic nature of source areas, which are distributed based on their mechanical resistance to abrasion, chemical alteration, and the morphology of the riverbed. The findings from this research contribute significantly to the field of sedimentology and integrated river management